Controlling the structure of arborescent carbon nanotube networks for advanced rubber composites. (28th July 2018) - Kobashi, Kazufumi; Ata, Seisuke; Yamada, Takeo; Futaba, Don N.; Hata, Kenji
Abstract: We propose a method for controlling the arborescent structure of long carbon nanotubes (CNTs) to harness their intrinsic properties in advanced rubber composites. Our method of structural control was based on a wet-jet mill to vary the shear forces (20–150 MPa) applied to aligned single-wall CNTs in solution. As the pressure of jet mill increased, the resulting suspended CNTs changed from agglomerates of bundled "trunk"-like structures to a CNT "mesh"-like structure with a high degree of disentanglement and absence of the "trunk"-like structures. The sizes of the CNT agglomerates became small and the number increased with the pressure of jet mill, indicating that smaller "mesh"-like CNT structures were formed with shortening of CNTs. This knowledge was used to increase the electrical conductivity of a CNT-rubber composite, highlighting the need to optimize the disentanglement state of the CNTs for application towards composite materials. Thus we successfully fabricated a CNT rubber with higher electrical conductivity (1.4 × 10 −2  S/cm) by balancing the disentanglement and shortening of the CNTs at the jet mill pressure of 120 MPa. On the other hand, the higher pressure of 150 MPa resulted in the lowest conductivity (7.5 × 10 −4  S/cm) due to more extensive shortening of CNTs.